Implementing cultural diversity in arts organisations : why and how to use intercultural networking - Bomash, Elizaveta (Taideyliopiston Sibelius-Akatemia, 2021)
This qualitative research provides ideas for art managers regarding why and how to include intercultural networking as part of the plan to implement cultural diversity on an organisational level. Art organisations often consider cultural diversity in audience development programmes, guided by the cultural policy recommendations of accessibility, inclusivity, and representation. However, the increasing body of research suggests that organisations must embrace diversity as part of their operations to establish relationships with diverse audiences. This approach indicates that diversity management and change management should guide the implementation of cultural diversity in art organisations. One point where these two branches of management intersect is getting the existing staff on board with the diversity programme. This study aims to examine intercultural networking as an active tool for supporting cultural diversity in the art field. The instrumental case study explores an intercultural networking event organised by Culture Kids and Dörren for representatives of several cultural organisations in Helsinki. The findings showed that art professionals of local backgrounds experienced intercultural networking as an activity that inspired change from within, brought new ideas, and served as a signal mechanism for the field interest in cultural diversity. Art organisations can support intercultural networking by adopting a strategic perspective that treats diversity as a source of learning and facilitating the right environment for interaction.
Keywords: kulttuurienvälisyys; kulttuuri; taide; monikulttuurisuus; kulttuurienvälinen viestintä; taidehallinto; fi=taidehallinto|sv=Arts Management|en=Arts Management|